The actualization of the social media affordance for sociality in an informal learning environment: the case of Saudi Arabia - Almukhaylid, Maryam (Department of Information Systems, 2025)
Problem statement: Informal learning, which occurs outside formal educational institutions and is characterized by the learner's autonomy and self-direction, has not been afforded the same academic attention as its formal counterpart. Social media is being used as a tool for informal learning spaces in Saudi Arabia. Despite the growing use of social media platforms for learning, researchers have yet to reach a consensus on the specific informal learning behaviours exhibited by learners who use technology to facilitate their education. Consider explaining how social media affordances for sociality may be actualized for the greatest benefit of learners in the future. Additionally, it is crucial to examine the factors that influence the realization of these affordances and how they impact informal learning behaviours. Purpose of the Study: The primary objective of this study was to investigate the actualization of social media affordances for sociality among informal learners in Saudi Arabia. The study examined the influencing factors and the effects of actualization on informal learners. To achieve this objective, the study identified the social media affordances for sociality in the informal learning environment and elucidated the actualization process. Additionally, it discussed the main factors influencing actualization and the effects of the actualization process. Research methodology: To deepen our comprehension of informal learners' experiences, this research investigates their interactions within the actual context of informal learning via social media platforms. Employing explanatory methods within the framework of an interpretivist paradigm, the study aims to interpret and understand the nuances of their learning experiences. The study also drew upon affordance theory and social cognitive theory as a lens to understand the social media affordances for sociality actualization in informal learning contexts. Semistructured interviews, focus group discussions, online observations, and documents were employed as data gathering methods in this study. For the study, participants among informal learners in Saudi Arabia were selected using purposive and snowball sampling techniques. The thematic analysis method was employed in this study to analyse the collected data. Key findings: The research revealed that informal learners in Saudi Arabia effectively leverage the affordances for sociality provided by social media platforms to meet their learning requirements. However, the findings show that there are personal, environmental and technological factors influencing Saudi informal learners' actualization of the social media affordances for sociality. The study identified and explained the key affordances for sociality that are especially pertinent to Saudi informal learners, finding that informal community of practice, enrichment of knowledge and skills, development of personal branding, and enhancement of reputation constitute the principal outcomes of these affordances' actualization. Contribution: This study has made a contribution to knowledge, theory, and practice. Initially, the study suggests theoretical propositions that explain how informal learners actualize social media affordances for sociality. The findings could provide valuable insights for comparable contexts in other countries. The study use of affordance theory in conjunction with social cognitive theory to explain the observed phenomena represents a significant theoretical contribution. It discusses the affordances for sociality of social media from an IS research standpoint. Furthermore, the research offers practical ways for fostering socialization on social media platforms as a tool of informal learning. These insights have the potential to be particularly beneficial for informal learners seeking to enhance their learning behaviours through social media. The study's insights into social media's role in informal learning can support initiatives that encourage Saudis to embrace continuous learning beyond formal education. This aligns with the broader goal of developing a knowledge-based society and social skills that are in line with Saudi Vision 2030.